2010
DOI: 10.1007/s10811-010-9622-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polysaccharides from Hypnea spinella (Gigartinales) and Halopithys incurva (Ceramiales) and their effect on RAW 264.7 macrophage activity

Abstract: Red algae have been reported to be an important source of polysaccharides with potential immunomodulatory properties. The objective of this study was to characterize the polysaccharides from Halopithys incurva and Hypnea spinella and to evaluate their effect on the synthesis of cytokines by murine cell line RAW 264.7 macrophages. Polysaccharides were obtained by N-cetylpyridinium bromide precipitation and characterized by Fourier transform-infrared spectroscopy. Their effect on the activity of RAW 264.7 macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…We demonstrated that TSP showed an inhibitory effect on HepG2 cells. The highest inhibitory rate was 66.8% at a concentration of 250 µg/mL, which was higher than that of spirulina polysaccharide [37] and Pavlova viridis polysaccharide [31]. Furthermore, the mechanism of TSP anticancer activity was mainly through inducing cell apoptosis rather than affecting the cell cycle and mitosis of HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that TSP showed an inhibitory effect on HepG2 cells. The highest inhibitory rate was 66.8% at a concentration of 250 µg/mL, which was higher than that of spirulina polysaccharide [37] and Pavlova viridis polysaccharide [31]. Furthermore, the mechanism of TSP anticancer activity was mainly through inducing cell apoptosis rather than affecting the cell cycle and mitosis of HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, these sulfated polysaccharides have been extensively studied because of their various biological activities, including their antitumor, anti-inflammation, and anticancer and immunomodulation activities [24,25,26,27,28]. Currently, immunomodulatory studies on sulfated polysaccharides from seaweeds have been performed mainly on polysaccharides from the brown algae Undaria pinnatifida , green algae Caulerpa lentillifera , and red seaweed Hypnea spinella [29,30,31]. However, the effect of microalgal sulfated polysaccharides on the human immune system has been less studied except in Phaeodactylum tricornutum , Chlorella stigmatophora , Pavlova viridis , Thraustochytriidae , and Spirulina [32,33,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Water extracts (WE) from AN, ECK, and JAN were obtained by suspending each powder in sterile distilled water (0.5%) under continuous stirring at 50 °C for 12 h and then filtered [9]. Polysaccharides were extracted from WE [64] and selectively precipitated with 2% (w/v) O - N -cetylpyridinium bromide (Cetavlon) [65]. Then, they were purified with 4 M NaCl, flocculated with 96% (v/v) ethanol and centrifuged (10,000 g for 10 min; Beckman Coulter Avanti J-26 XP, Indianapolis, IN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Modulation of the innate humoral and cellular immune system is one of the benefits suggested for algae (Vallejos-Vidal, Reyes-López, Teles, & MacKenzie, 2016). The role between nutrition and immune system is well recognized, and algae have been reported as a source of bioactive molecules with immunostimulant effects in aquaculture (Abdala-Díaz, Chabrillón, Cabello-Pasini, Gómez-Pinchetti, & Figueroa, 2011;Abdala-Díaz, Chabrillón, Cabello-Pasini, López-Soler, & Figueroa, 2010;Kumala, Wahjuningrum, & Setiawati, 2018). Modulation of the immune response of fish receiving dietary algae has been investigated with contrasting results.…”
Section: Introductionmentioning
confidence: 99%